Emotional Labour Dalam Pelayanan dan Pengaruhnya Kepada Pelanggan di Kafe Yege Resto Di Salatiga - Ricky Arnold Nggili; Ignatius Bias Galih Prasadhya; Dinda Rahma Hidayah; Abdenigara Ahma Hutari (Journal of Economics Business Finance and Accounting, 2024)
This study aims to analyze the impact of employees’ emotional labour on customer experience at Yege Resto & Cafe in Salatiga. The research is grounded in the significance of employee–customer interactions in the culinary industry, where both verbal and non-verbal service quality play a critical role in determining customer satisfaction and loyalty. A qualitative approach with a descriptive method was employed, using non-participant observation of five employees and several customers over three operational days. Data were collected through observations of employee behavior, customer responses, and feedback regarding service and product quality. The findings reveal that employees who successfully apply deep acting—demonstrating genuine friendliness, empathy, and interpersonal communication—are able to create positive customer experiences, enhancing comfort and trust. In contrast, service interactions perceived as merely formal or lacking in empathy tend to weaken the emotional connection with customers. Additionally, purchasing decisions are influenced not only by service quality but also by factors such as pricing and perceived product value. These findings emphasize that a combination of emotional labour skills and responsive service strategies is essential for building customer satisfaction and loyalty, while also strengthening Yege Resto & Cafe’s brand image amid intense competition in the café industry.